If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -12 = 4x + 20 Reorder the terms: -12 + 8x = 4x + 20 Reorder the terms: -12 + 8x = 20 + 4x Solving -12 + 8x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 8x + -4x = 20 + 4x + -4x Combine like terms: 8x + -4x = 4x -12 + 4x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 4x = 20 + 0 -12 + 4x = 20 Add '12' to each side of the equation. -12 + 12 + 4x = 20 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 20 + 12 4x = 20 + 12 Combine like terms: 20 + 12 = 32 4x = 32 Divide each side by '4'. x = 8 Simplifying x = 8
| x=y^2-5 | | 3y+4=5y-6 | | 5x^2+2y^2=10 | | 5*(m+1)-3*(2m+1)=4*(5-m) | | 3m=7m-16 | | x+487-69=3865 | | p(x)=80-3x | | X+9=8x^2+16 | | -30u+(-6u)= | | 8x^2+16x= | | 2x+4x+40=180 | | 2(y-1)+4y=8 | | 15x+20(x-5)=285 | | 4x^2+9x-9= | | 9x^2-7x-116=0 | | 9y-3y-2y=28 | | -1=-3x-2 | | Y=-3(0)-2 | | 2z-6z+1=9 | | Y=-3(-1)-2 | | 2d+8=2 | | 5w+3w+2w=60 | | 5k+2(k+1)=24 | | -7m-m+1=9 | | 3z-z=10 | | 4x^2+5x=-3 | | 8-y=9 | | -3-y=-1 | | -2-y=-1 | | 6=-3(x-5) | | 63=5x^2-26x | | x-(-38)=43 |